Fatores ambientais associados à epidemiologia da hantavirose em Minas Gerais no período de 2002 a 2009 - Oliveira, Lilia Beatriz (2012)
Demographic and environmental changes may be considered the main causes that favor the emergence of new diseases. Changes in land use for agriculture imply sharing space with vectors and reservoirs, allowing the emergence and reemergence of infectious diseases. Hantaviruses was first recognized in Brazil in 1993 and, in Minas Gerais in 1998. Hantaviruses, emerging zoonosis of worldwide distribution, has its transmission related to close contact with viral particles are shed in feces and urine of rodents. The aim of the study was to determine the epidemiological profile, analyze the spatial and temporal distribution of Hantavirus as well as verify the correlation between land use, climatic factors, demographic and epidemiological in Minas Gerais, using the database of cases of hantaviruses by the Information System for Notification Diseases by Ministry of Health in the period from 2002 to 2009. A total of 209 cases were assessed, the largest number of cases in 2005. The incidence ranged from 7.63 to 20.79 / 10 million. The cases were concentrated in geographical regions of Triângulo Mineiro and Alto Paranaíba. The case fatality rate ranged from 20% to 52%. Men, caucasians, aged 21-40 years with 4-7 years of education were the most affected. The majority of cases occurred in rural areas and during occupational activities. This study confirmed the existence of a seasonal pattern of hantavirus in Minas Gerais being incident in drier months of the year. The cases were concentrated in areas of cerrado (savannah) and showed strong positive correlation with beans’ crops (South / Southwest) and soybeans in Triângulo Mineiro. Results obtained by calculating the global Moran index for the studied variables, expressed the existence of positive spatial correlation for hantaviruses in Minas Gerais. We conclude that control of hantaviruses requires a situational diagnosis with the involvement of multiple professionals aiming to establish policies to prevent and control cases, especially related to occupational occurrences.